Factors Associated with the Prevalence of Precarious Positions in Canadian Libraries: Statistical Analysis of a National Job Board - Henninger, Ean; Brons, Adena; Riley, Chloe; Yin, Crystal (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective - To collect and share information about the prevalence of precarious work in libraries and the factors associated with it.Methods - The authors collected and coded job postings from a nationwide job board in Canada for two years. Descriptive and inferential statistics were used to explore the extent of precarity and its relationship with job characteristics such as job type, institution type, education level, and minimum required experience.Results - The authors collected 1,968 postings, of which 842 (42.8%) were coded as precarious in some way. The most common types of precarious work were contracts (29.1% of all postings) and part-time work (22.7% of all postings). Contracts were most prevalent in and significantly associated with academic libraries and librarian positions, and they were most often one year in length. Both on-call and part-time work were most prevalent in school libraries and for library technicians and assistants, and they were significantly associated with all institution types either positively or negatively. Meanwhile, precarious positions overall were least prevalent in government and managerial positions. In terms of education, jobs requiring a secondary diploma or library technician diploma were most likely to be precarious, while positions requiring an MLIS were least likely. The mean minimum required experience was lower for all types of precarious positions than for stable positions, and the prevalence of precarity generally decreased as minimum required experience increased.Conclusion - The proportion of precarious positions advertised in Canada is substantial and seems to be growing over time. Based on these postings, employees with less experience, without advanced degrees, or in library technician and assistant roles are more likely to be precarious, while those with managerial positions, advanced degrees, or more experience, are less likely to be precarious. Variations in precarity based on factors such as job type, institution type, education level, and minimum required experience suggest that employees will experience precarity differently both within and across library systems.